American Archias: Cicero and The Souls of Black Folk. (28th November 2020) - Withun, David
Abstract: While scholars have long noted the classical influences apparent in the style and thought of W. E. B. Du Bois, there has been little sustained discussion of the nature of these influences and their manifestations in his writings. This article seeks to correct that absence through an examination of the influence of Cicero's Pro Archia poeta on Du Bois's most well-known work, The Souls of Black Folk . Though Du Bois mentions many other authors in Souls, the Pro Archia is the only work of another author mentioned by name as a source for Du Bois's thought. Extrapolating from this explicit reference to the Pro Archia as well as numerous other references to and influences by Cicero's works throughout Du Bois's oeuvre, I posit a two-fold influence of the Pro Archia on Souls as Du Bois draws upon the dual argument in Cicero's work. First, Du Bois seeks to defend the civil rights of African Americans, drawing on Cicero's argument for the legal status and citizenship rights of the poet Archias. Both Cicero and Du Bois go beyond mere legal argumentation, however, to provide a defence of the necessity of the liberal arts and a celebration of poets and their work .